2022
DOI: 10.3390/ani13010082
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Diversity of Intrauterine Anaerobic Microbiota in Dairy Cows with Clinical and Subclinical Endometritis

Abstract: The aim of the study was to characterize the dynamics of anaerobic cultivable postpartum microbiota in the uterus of dairy cows. In total, 122 dairy cows were enrolled and sampled on day 0 (day of calving) and on days 3, 9, 15, 21, and 28 postpartum (pp). Samples were cultivated anaerobically and analyzed by MALDI-TOF MS. In total, 1858 isolates were recovered. The most prevalent facultative anaerobic genera were Trueperella (27.8%), Streptococcus (25.4%), and Escherichia (13.1%). The most prevalent obligate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many strictly anaerobic bacteria, such as Bacteroides , Lactobacillus , and Prevotella were detected in our study and suggested that the microbiota in milk is not only related to the external environment. The high abundance of typically gut-associated microbes in the two groups confirmed that a part of the milk flora originated from the gastrointestinal tract, and this portion of gut-related bacteria would enter the breast, promoted by hormonal changes during and after pregnancy [ 11 , 51 ]. In the two groups, both the fluctuations in lactation time and the differences in the abundance of some typically gut-associated microbes showed that the physiological changes of dairy cows affect the diversity of milk microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many strictly anaerobic bacteria, such as Bacteroides , Lactobacillus , and Prevotella were detected in our study and suggested that the microbiota in milk is not only related to the external environment. The high abundance of typically gut-associated microbes in the two groups confirmed that a part of the milk flora originated from the gastrointestinal tract, and this portion of gut-related bacteria would enter the breast, promoted by hormonal changes during and after pregnancy [ 11 , 51 ]. In the two groups, both the fluctuations in lactation time and the differences in the abundance of some typically gut-associated microbes showed that the physiological changes of dairy cows affect the diversity of milk microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Lactobacillus , some genera showed higher abundance in the colostrum stage in the two groups, such as Alcaligenes , Streptococcus , Veillonella , Blautia , etc. In addition to nutritional composition changes over the transition period, hormonal and metabolic changes are also observed in cows [ 11 , 55 ], which may contribute to the differences in genera in colostrum. The alpha diversity also validated that the differences in milk diversity between the first three days and that of other time points were more obvious in the PC group ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, it is important to establish the condition of the organs of the reproductive system of cows before insemination. This is due to the fact that according to foreign authors (Wagener et al, 2017;Ballas et al, 2022;Pascottini et al, 2023), during this period subclinical inflammatory processes are diagnosed, namely endometritis, salpingitis, or ovariitis. After applying the prescribed treatment, the duration of the service period decreased by an average of 25%.…”
Section: Table 1 Comparison Of Biochemical Parameters Of Blood In Cow...mentioning
confidence: 99%